2009
DOI: 10.1242/dev.033183
|View full text |Cite
|
Sign up to set email alerts
|

The maternal-to-zygotic transition: a play in two acts

Abstract: All animal embryos pass through a stage during which developmental control is handed from maternally provided gene products to those synthesized from the zygotic genome. This maternal-to-zygotic transition (MZT) has been extensively studied in model organisms, including echinoderms, nematodes, insects, fish,amphibians and mammals. In all cases, the MZT can be subdivided into two interrelated processes: first, a subset of maternal mRNAs and proteins is eliminated; second, zygotic transcription is initiated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
943
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,008 publications
(992 citation statements)
references
References 88 publications
29
943
1
2
Order By: Relevance
“…However, Kanka and co-authors (Kanka et al 2009) have demonstrated transcriptional activity of a few genes in 4-cell stage bovine embryos. This increase in transcription of selected genes, prior to the global activation at the 8 to 16-cell stage has been referred to as the "minor genome activation" and has been reported in several species [for review see (Tadros & Lipshitz 2009). Further studies are needed to determine if the increase in H3R26me2 levels observed in the 4-cell embryos in the present study are associated with minor activation of the embryonic genome.…”
Section: Discussionmentioning
confidence: 95%
“…However, Kanka and co-authors (Kanka et al 2009) have demonstrated transcriptional activity of a few genes in 4-cell stage bovine embryos. This increase in transcription of selected genes, prior to the global activation at the 8 to 16-cell stage has been referred to as the "minor genome activation" and has been reported in several species [for review see (Tadros & Lipshitz 2009). Further studies are needed to determine if the increase in H3R26me2 levels observed in the 4-cell embryos in the present study are associated with minor activation of the embryonic genome.…”
Section: Discussionmentioning
confidence: 95%
“…We find that genes with relatively high methylation density are significantly enriched for functions associated with organ and anatomical structure development (Table 3), which taken together with the findings discussed in the preceding paragraph suggests that genes with a role in later stages of development may be suppressed by methylation at stage 5. Embryonic stage 5 in Drosophila coincides with the beginning of zygotic gene expression (Foe and Alberts 1983;Tadros and Lipshitz 2009). The relative abundance of cytosine methylation at this stage, its apparent effect on gene expression, and its association with genes that play a role in development, prompt us to speculate that methylation participates in gene regulation at the maternal-zygotic transition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the global TSS use patterns seem remarkably stable across different somatic cell types, although differential TSS selection is evident at individual promoters between specific cell types [27]. Also, the purpose of a separate TSS selection code in oocyte is unclear at present: it may be used as an efficient way of genome-wide change of transcriptional repertoire between the oocyte and somatic cells -the most dramatic of such changes in the life cycle of Metazoa [107].…”
Section: Overlapping Transcription Initiation Codes: Thousands Of 2-imentioning
confidence: 99%